A systematic analysis of the ethnopharmacological relevance of an Indian traditional plant, Hemidesmus indicus (L.) R.Br. for the past 10 years - M. Divya Darshini, M. S. Sreelakshmi, J. Adithya, N. S. Aryaputhri, P. K. Lakshmi, Lekshmi R. Nath (Journal of Applied Pharmaceutical Science, 2024)
Hemidesmus indicus (L.) R.Br., an Indian traditional plant belonging to the family Apocynaceae is a climber growing in the Indian subcontinent. The plant popularly known as “Anantmool,” is a vital ingredient in medicinal formulations (Ayurveda, Siddha, and Unani). In the present study, we performed a systematic review analysis of the research progress of H. indicus (L.) R.B.R. conducted during the past 10 years. The data was retrieved from several online databases and search engines- PubMed, Google Scholar, Scopus, and Science Direct. Since the 20th century, it has been used as a traditional folk remedy for ailments such as snake bites, leprosy, arthritis, bacterial infections, syphilis, fever, headache, dysentery, and diarrhoea. The major pharmacological properties of H. indicus include antioxidant, anti-diabetic, anti-cancer, anti-ulcerogenic, anti-inflammatory, anti-microbial, hepatoprotection, neuroprotection, cardioprotection, and nephroprotection. The phytochemical screening of H. indicus identified the presence of flavonoids, terpenoids, tannins, steroids, and lignans. Several formulations of H. indicus are commercially available to the public as herbal powder and topical creams/oils. Evidence supports that H. indicus can be potentially explored for further drug discovery process in terms of bioactive against various disease conditions thus helping in the clinical setting to discover promising drugs.
Keywords: Hemidesmus indicus (L.) R.Br., Indian Sarsapilla, anantmool, preclinical studies, Hemidesmus, herbal remedy, ayurvedic preparations